The genus Dicrania LePeletier & Audinet-Serville, 1828 (Coleoptera: Scarabaeidae: Melolonthinae: Macrodactylini) from Colombia with the description of a new species - Clavijo-Bustos, Julián; Moreno, Jhon Cesar Neita; Fuhrmann, Juares (Zootaxa, 2024)
The genus Dicrania LePeletier & Audinet-Serville, 1828 (Coleoptera: Scarabaeidae: Melolonthinae: Macrodactylini) is widely distributed in South America, but only one species was previously known from Colombia: Dicrania laevipennis Moser, 1921. Here the genus is revised for Colombia and Dicrania chimu Clavijo-Bustos, Neita Moreno, & Fuhrmann, new species is described from the Llanos Orientales (Orinoquía) region and a new departmental record for D. laevipennis is documented.